Comparative analysis of constitutional rights and their implementation in Kazakhstan and other CIS countries: problems and prospects - Zhamankarayeva, G.; Baizhanov , Y.; Yarilkhapova, Sh. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The research examines constitutional rights protections within eight CIS: Russia, Kazakhstan, Ukraine, Belarus, Moldova, Tajikistan, Armenia, and Kyrgyzstan. The research aims to examine dissimilarities and similarities in legal implementation while identifying rights promotion and barrier factors to produce international standard-compliant execution recommendations. The research utilizes an interdisciplinary approach combining comparative legal, normative historical and legal methods with content-based evaluations of legislative documents, constitutional provisions and judicial decisions and expert evaluations. Research findings indicate that Ukraine and Moldova actively use individual constitutional complaint mechanisms as the Constitutional Courts show considerable independence. Belarus and Tajikistan struggle to protect rights because their judicial systems answer to the executive branch. Kazakhstan and Russia are characterized by strong executive power and a focus on maintaining stability, accompanied by restrictions on certain civil liberties. Armenia and Kyrgyzstan work to achieve democratization through their institutions although they face both institutional and political instability. The research presents recommendations which aim to enhance judicial protection of rights and to integrate international norms into national laws as well as to promote independence in constitutional supervision. The research outcomes present practical value by enabling their application for legal institution reform and human rights program development throughout the post-Soviet region.